1995
DOI: 10.1074/jbc.270.21.12839
|View full text |Cite
|
Sign up to set email alerts
|

The Staphylococcus aureus Enterotoxin B Superantigen Induces Specific T Cell Receptor Down-regulation by Increasing Its Internalization

Abstract: Superantigens are able to stimulate T lymphocyte populations expressing T cell antigen receptors (TCR) belonging to particular V beta families. Moreover, the presence of these superantigens may induce long term unresponsiveness (anergy) of these sensitive cells. Some bacterial toxins are potent superantigens. We have analyzed in vitro the capacity of some Staphylococcus aureus enterotoxin superantigens to modulate T cell antigen receptor expression and the cellular mechanisms involved. Staphylococcus enterotox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
44
2

Year Published

1997
1997
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(48 citation statements)
references
References 43 publications
2
44
2
Order By: Relevance
“…This finding is not in accordance with the findings of Fleischer and Schrezenmeier [23] and Spertini et al [27], who reported that a T-cell clone could respond directly to SEA and SEB (which are in different class than SEE) in the absence of accessory cells. This finding also contrasts with Niedergang's et al [24], observation of a biological effect of SEB on Vβ3-transfected Jurkat cells in the complete absence of accessory cells. It is worth noting that the fluorescently labeled SEE was able to reduce TCR Vβ8 protein expression and induce expression of the luciferase gene with the same efficiency as unlabeled SEE.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…This finding is not in accordance with the findings of Fleischer and Schrezenmeier [23] and Spertini et al [27], who reported that a T-cell clone could respond directly to SEA and SEB (which are in different class than SEE) in the absence of accessory cells. This finding also contrasts with Niedergang's et al [24], observation of a biological effect of SEB on Vβ3-transfected Jurkat cells in the complete absence of accessory cells. It is worth noting that the fluorescently labeled SEE was able to reduce TCR Vβ8 protein expression and induce expression of the luciferase gene with the same efficiency as unlabeled SEE.…”
Section: Discussioncontrasting
confidence: 56%
“…At 1 ng/mL SEE, measurable cell associated SEE is essentially at background levels. This finding is in contrast to what has been reported by others that did not observe any binding of SEB to T cells [24]. …”
Section: See Has Higher Binding Affinity To Accessory Cells Than To Tcontrasting
confidence: 56%
“…Conventional T cells are also known to downregulate their TCRs upon exposure to SEB. 54 By contrast, SEBactivated mouse iNKT cells remained detectable at all time points examined. Human iNKT cells also clearly lost their TCR surface expression in response to aGC, but not SEB, which followed a different kinetics in comparison with mouse iNKT cells-that is they were still undetectable at least up until day 7.…”
Section: Human Inkt Cells Are Activated By Bacterial Sagsmentioning
confidence: 88%
“…In theory, TCR down-regulation can be accomplished by an increase in the endocytic rate constant, a decrease in the exocytic rate constant, or a combination of both. Most studies found that TCR down-regulation is caused by an increase in the endocytic rate constant after TCR triggering (13,15,17,28,33); however, some studies indicated that TCR ligation induces TCR down-regulation by a reduction in the exocytic rate constant rather than by an increase in the endocytic rate constant (16). Divergent models for TCR degradation also exist.…”
mentioning
confidence: 99%
“…Thus, at steady state a certain amount of TCR is endocytosed, while at the same time an equal amount of TCR is exocytosed. Several studies seem to agree that the constitutive endocytic rate constant for the TCR in resting T cells is ϳ0.01 min Ϫ1 , meaning that 1% of the cell surface-expressed TCR is internalized each minute (11,(15)(16)(17). However, whether the TCR is endocytosed and further processed as an intact receptor or as individual subunits with different endocytic, exocytic, and degradation rate constants remains unclear.…”
mentioning
confidence: 99%